Phenolic Compounds from Cestrum aurantiacum - Yin, Hai-Chuan; Liao, Zhen; Hu, Lin; Hu, Qun (Asian Journal of Chemistry, 2012)
A new phenolic compound (1), together with eight known compounds (2-9) were isolated from the leaves and stems of Cestrum aurantiacum. The structure was elucidated on the basis of extensive NMR and mass spectral means. The anti-HIV-1 and antioxidant activity of (1) was evaluated and showed weak anti-HIV-1 activity with Therapeutic Index 24.1 and antioxidant activity with an IC50 value of 3.68 μg/mL.